1995
DOI: 10.1016/0921-4526(94)00535-4
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting energy gap in URu2Si2

Abstract: Superconducting energy gap in URu2Si2Samuely, P.; Szabo, P.; Flachbart, K.; Mihalik, M.; Menovsky, A.A. Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please Ask the Library: http://uba.uva.nl/en/contact, or a letter to: Library of the University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
1
8
1
Order By: Relevance
“…These observations are consistent with previous conventional mechanical PCS reports. [29][30][31][32] Even though the conductance peaks observed here are asymmetric and offset with respect to E F , they are very similar to results of point-contact Andreev-reflection studies of superconductors (Ref. 27 and references within), possibly indicating a mean-field like particle-hole condensation and macroscopic coherence build up in the HO state of URu 2 Si 2 .…”
supporting
confidence: 87%
See 1 more Smart Citation
“…These observations are consistent with previous conventional mechanical PCS reports. [29][30][31][32] Even though the conductance peaks observed here are asymmetric and offset with respect to E F , they are very similar to results of point-contact Andreev-reflection studies of superconductors (Ref. 27 and references within), possibly indicating a mean-field like particle-hole condensation and macroscopic coherence build up in the HO state of URu 2 Si 2 .…”
supporting
confidence: 87%
“…Because the resistivity jump is associated with the FS reorganization and thus a sudden removal of parts of the FS at the HO transition, 9,12 the observed side feature in G(V) should be intrinsic to URu 2 Si 2 and could be due to a change in the electronic DOS as the FS reconstructs. Previous conventional PCS measurements have reported that the onset temperature of PCS features differs from T HO , 30,31 possibly due to a local pressure induced at the point-contact area, which may affect properties locally. 31 On the other hand, the appearance of a pseudogap due to incoherent fluctuations of the HO has been proposed to explain observations of gap-like features several degrees above T HO .…”
mentioning
confidence: 98%
“…Hasselbach et al and Samuely et al [4], [5] found that their PC data were described slightly better with d-wave symmetry, while De Wilde et al [6] from their data suggest the absence of zeros in the gap. These measurements either were carried out only for the c-direction in a single crystal [4], [6] or on a polycrystalline sample [5], which does not allow an unequivocal conclusion concerning gap anisotropy. Furthermore, these measurements did not show the unmistakable signature of AR, namely a double-minimum structure in the differential resistance dV /dI, which should be present whenever besides AR there is a finite probability of ordinary reflection [3].…”
mentioning
confidence: 92%
“…Far-infrared spectroscopy shows a low energy 6 meV gap develop below T HO [54] as well as spectral weight transfer on the 16 meV scale associated with hybridization gapping and the onset of coherence around 75K [55]. Point contact tunneling spectroscopy observes an 11-14 meV gap opening with a mean-field onset above T HO at ∼22-26K [56,57,58,59], but also as high as 34K [60], that is interpreted [59,60,61] as hybridization gapping associated with Kondo coherence, and thus implying an insensitivity of the technique to any signature of a HO/AF related gap. Scanning tunneling spectroscopy observes both the slow development of a broad asymmetric Fano lineshape profile over a 100 meV energy scale beginning <100K that is associated with Kondo coherence, and a much narrower 4-5 meV gap at E F with a BCS-like T -dependence onsetting around 16K [34].…”
Section: Fermi Surface Gappingmentioning
confidence: 93%